2014
DOI: 10.1016/j.ttbdis.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Ixodes ricinus and Borrelia prevalence at the Arctic Circle in Norway

Abstract: The distribution limit of Ixodes ricinus ticks in northwestern Europe (Brønnøy, Norway, 1° south of the Arctic Circle), has been known since the 1930s. To reconfirm this finding and extend studies in the areas adjacent to the Arctic Circle (66°33' N), ticks were collected from dogs and cats in 8 districts in northern Norway from 64°56' N to 68°48' N. We detected 549 I. ricinus, 244 (44%) of them in Brønnøy district, and 305 (range 6-87 ticks) in 7 districts in the northern part of the study area. The prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 25 publications
1
30
0
1
Order By: Relevance
“…In northern Norway, B. afzelii is particularly abundant (60–95% of the Borreli a‐infected ticks) with B. garinii and/or B. valaisiana in the remaining proportion. Except for its presence in a single tick , B. burgdorferi s.s. has not been detected by PCR in northern Norway .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In northern Norway, B. afzelii is particularly abundant (60–95% of the Borreli a‐infected ticks) with B. garinii and/or B. valaisiana in the remaining proportion. Except for its presence in a single tick , B. burgdorferi s.s. has not been detected by PCR in northern Norway .…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact tick distribution limit in northwestern Europe has not been precisely established, it is well known that I. ricinus occurs in the northern region of Norway . Hvidsten et al showed that northwards from the district neighbouring Brønnøy (65° 28′ N) in Nordland County, there was a negative gradient of the number of I. ricinus collected from pets. Furthermore, the prevalence of B. burgdorferi s.l.…”
mentioning
confidence: 99%
“…This applies to I. ricinus in Norway [38, 39] and Sweden [40]. In Sweden I. ricinus has increased its abundance and geographical distribution northwards during the last two decades [33].…”
Section: Discussionmentioning
confidence: 99%
“…Вид распространен пре-имущественно южнее и западнее границ Рес-публики Карелия, при этом самые северные находки отмечены в районе полярного круга [Hvidsten et al, 2014]. Крупные природные пар-ки европейских городов с относительно низкой антропогенной нагрузкой делают возможным прохождение здесь всего жизненного цик-ла I. ricinus и создают определенную эпидемио-логическую напряженность [Junttila et al, 1999;Foldvari et al, 2011;Greenfield, 2011;Jennett et al, 2013;Rizzoli et al, 2014].…”
Section: Discussionunclassified